2018
DOI: 10.1016/j.watres.2018.01.053
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of virus processing on human norovirus GI and GII persistence during disinfection of municipal secondary wastewater effluent

Abstract: Noroviruses cause significant global health burdens and waterborne transmission is a known exposure pathway. Chlorination is the most common method of disinfection for water and wastewater worldwide. The purpose of this study was to investigate the underlying causes for discrepancies in human norovirus (hNoV) resistance to free chlorine that have been previously published, and to assess hNoV GI and GII persistence during disinfection of municipal secondary wastewater (WW) effluent. Our results reveal that choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…As a result of high volumes of dissolved NH 3 and organic matter (OM) in the wastewater, toxic residues called chloramines are produced, along with substitute derivatives for the disinfection treatment process; thus, causing ecotoxicological effects ( Luan et al, 2020 ; Verbyla and Mihelcic, 2015 ). The studies of Dunkin et al (2018) reported the reasons for the resistance of variable human noroviruses (hNoV) to free chlorine and examined the endurance of GI and GII fragments of hNoV at the time of disinfection of public wastewater effluent. As observed, prior to the cultivation of viruses in wastewater, the selection of the hNoV purification method assists in gaining significant disinfection outcomes.…”
Section: Approaches To Processes For the Removal Of Sars-cov-2 In Wastewater Processing Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of high volumes of dissolved NH 3 and organic matter (OM) in the wastewater, toxic residues called chloramines are produced, along with substitute derivatives for the disinfection treatment process; thus, causing ecotoxicological effects ( Luan et al, 2020 ; Verbyla and Mihelcic, 2015 ). The studies of Dunkin et al (2018) reported the reasons for the resistance of variable human noroviruses (hNoV) to free chlorine and examined the endurance of GI and GII fragments of hNoV at the time of disinfection of public wastewater effluent. As observed, prior to the cultivation of viruses in wastewater, the selection of the hNoV purification method assists in gaining significant disinfection outcomes.…”
Section: Approaches To Processes For the Removal Of Sars-cov-2 In Wastewater Processing Plantsmentioning
confidence: 99%
“…As observed, prior to the cultivation of viruses in wastewater, the selection of the hNoV purification method assists in gaining significant disinfection outcomes. The tertiary wastewater treatment stage should employ free chlorine disinfection, which is beneficial for protecting public health from virus pollution ( Dunkin et al, 2018 ).…”
Section: Approaches To Processes For the Removal Of Sars-cov-2 In Wastewater Processing Plantsmentioning
confidence: 99%
“…At WWTPs, disinfection intensity, determined by some operational parameters in a disinfection reactor (e.g., contact time and initial concentration of the disinfectant), is suitable as a parameter at a CCP for monitoring because the log reduction value (LRV) of waterborne viruses is proportional to it. 12,13 Under the multiple barrier concepts, 14,15 CLs at a disinfection step must be determined in advance so that a target LRV is achieved. However, the fluctuation of wastewater quality affects the LRV in a disinfection process 13,16,17 because contaminants in wastewater consume disinfectants.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Under the multiple barrier concepts, 14,15 CLs at a disinfection step must be determined in advance so that a target LRV is achieved. However, the fluctuation of wastewater quality affects the LRV in a disinfection process 13,16,17 because contaminants in wastewater consume disinfectants. A method to determine the CL has not been developed, so a flexible prediction model of a virus LRV needs to be established to determine CLs based on water quality information as model variables, which enables WWTP operators to identify the disinfection intensity (e.g., disinfectant concentration and contact time) so as to achieve the target LRV.…”
Section: Introductionmentioning
confidence: 99%
“…The challenge posed by these infections to global health is aggravated by factors such as immune-compromise and globalization of the food industry (4,5). The high diversity of genetic and antigenic noroviruses complicate the development of vaccines and therapies required to combat these challenges (6,7). Human norovirus belongs to the Caliciviridae family, and possesses a single-stranded positive-sense RNA genome (7.5 kb) with three open reading frames (ORFs) that encode different proteins (8).…”
Section: Introductionmentioning
confidence: 99%